Analisis Pengendalian Persediaan Bahan Pakan Untuk Ternak Ayam Broiller Dengan Metode Economic Order Quantity (EOQ) Pada Pt. Mitra Sinar Jaya Dikecamatan Boawae - Wawo, Mateus; Langga, Lambertus; Tanusi, Gabriel (SCIENTIFIC JOURNAL OF MANAGEMENT AND BUSINESS (SJMB), 2021)
This type of research is descriotive quantitative research, namely the type of research that describes the research variables without testing the hypothesis. This study describes and explain that direct observations were made to determine the control of feedstuff supplies as material for broiler chickens at PT. Mitra Sinar Jaya in Boawae District. The results of this study indicate that (1) the cost of controlling feedstuffs applied by PT. Mitra Sinar Jaya to get the maximum benefit from operational supplies. This company will greatly affect the cost of inventory incurred, so that the frequency of ordering feed ingredients and the number of orders per year affect the storage costs each year, (2) the efficiency of the supply of feed ingredients in the company can be improved with the Economic Order Quantity (EOQ) model, because in the use of the Economic Order Quantity (EOQ) method the company. So the company should do the Economic Order Quantity (EOQ) mthod, because by applying the EOQ method, the inventory costs and production process can be optimized and companies must also pay attention in the two components of inventory costs, namely order costs snd storage costs. These two cost components ae the company’s main reference in determining its inventory control policies.